2023
DOI: 10.1101/2023.06.19.545539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early life adversities affect expected value signaling in the adult brain

Abstract: Background: Early adverse experiences are assumed to affect fundamental processes of reward learning and decision-making. However, computational neuroimaging studies investigating these circuits are sparse and limited to studies that investigated adversities retrospectively in adolescent samples. Methods: We used prospective data from a longitudinal birth cohort study (n=156, 87 females, mean age=32.2) to investigate neurocomputational components underlying reinforcement learning in an fMRI-based passive avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
1
0
0
Order By: Relevance
“…The third adversity factor mostly reflected maternal stimulation. Similar to our previous work with a larger sample ( 50 ), we found that the first adversity factor was associated with higher scores in all psychopathology measures except for somatic problems (all p < 0.05, Bonferroni-corrected, Supplementary material S6 ). We did not identify any association between psychopathology measures and the second and third adversity factors, although the latter association was significant in the larger sample ( 50 ).…”
Section: Resultssupporting
confidence: 87%
“…The third adversity factor mostly reflected maternal stimulation. Similar to our previous work with a larger sample ( 50 ), we found that the first adversity factor was associated with higher scores in all psychopathology measures except for somatic problems (all p < 0.05, Bonferroni-corrected, Supplementary material S6 ). We did not identify any association between psychopathology measures and the second and third adversity factors, although the latter association was significant in the larger sample ( 50 ).…”
Section: Resultssupporting
confidence: 87%